The Influence of Social Involvement, Neighborhood Aesthetics, and Community Garden Participation on Fruit and Vegetable Consumption - Litt, Jill S. (American Public Health Association, 2011)
Objectives. We considered the relationship between an urban adult population's fruit and vegetable consumption and several selected social and psychological processes, beneficial aesthetic experiences, and garden participation. Methods. We conducted a population-based survey representing 436 residents across 58 block groups in Denver, Colorado, from 2006 to 2007. We used multilevel statistical models to evaluate the survey data. Results. Neighborhood aesthetics, social involvement, and community garden participation were significantly associated with fruit and vegetable intake. Community gardeners consumed fruits and vegetables 5.7 times per day, compared with home gardeners (4.6 times per day) and nongardeners (3.9 times per day). Moreover, 56% of community gardeners met national recommendations to consume fruits and vegetables at least 5 times per day, compared with 37% of home gardeners and 25% of nongardeners. Conclusions. Our study results shed light on neighborhood processes that affect food-related behaviors and provides insights about the potential of community gardens to affect these behaviors. The qualities intrinsic to community gardens make them a unique intervention that can narrow the divide between people and the places where food is grown and increase local opportunities to eat better.